Implementasi Rencana Kerja Pemerintah Gampong PEMENDAGRI No 114 Tahun 2014 Kabupaten Aceh Barat - Fanny Nur Annisah; Safrida Safrida (CV. Ulil Albab Corp, 2022)
This article or article aims to understand how to implement the gampong annual development plan in formulating development strategies and policies as well as formulating the Gampong Government Work Plan program for 1 (one) year. The problem is focused on the obstacles that occur during the preparation of the work plan of the gampong government by the DPMG agency and the gampong apparatus. In order to approach this problem, Goldratt's theoretical reference is used. Goldratt believes that every organization has obstacles that hinder performance, therefore Goldratt developed five sequential steps so that the process of repairing a problem that occurs is more focused and gives positive results for the previous system. (1) Identification of constraint resources on the system, (2) Designing strategies to fix constraints, (3) Linking other constraint sources to support the designed strategy, (4) Performing constraints to improve system constraint performance, (5) Returning to the first step for continuous improvement. The data were collected through Interview, Observation, and Documentation. This study concludes that in carrying out the work plan activities of the gampong government according to the Ministry of Home Affairs No. 114 of 2014 that in order to achieve national development priorities and targets, annual planning synergies are needed between the central government and local governments as well as between local governments. Then analyze the process of achieving the maximum implementation of gampong development programs/activities and are easily identified which refers to the Minister of Home Affairs Regulation No. 114 of 2014.